2011
DOI: 10.1182/blood-2011-02-335190
|View full text |Cite
|
Sign up to set email alerts
|

The ribosome-related protein, SBDS, is critical for normal erythropoiesis

Abstract: Although anemia is common in ShwachmanDiamond syndrome (SDS), the underlying mechanism remains unclear. We asked whether SBDS, which is mutated in most SDS patients, is critical for erythroid development. We found that SBDS expression is high early during erythroid differ- IntroductionShwachman-Diamond syndrome (SDS) is a rare multisystem disorder, primarily affecting the bone marrow, pancreas, and skeletal systems. 1,2 Hematologic abnormalities are a major cause for morbidity and mortality and include cytope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 53 publications
4
27
0
Order By: Relevance
“…[67][68][69] iPSCs derived from SDS patients manifest deficits in exocrine pancreatic and hematopoietic differentiation and enhanced apoptosis. 70 Deletion of murine Sbds resulted in early embryonic lethality.…”
Section: Shwachman-diamond Syndrome: Molecular Pathophysiologymentioning
confidence: 99%
“…[67][68][69] iPSCs derived from SDS patients manifest deficits in exocrine pancreatic and hematopoietic differentiation and enhanced apoptosis. 70 Deletion of murine Sbds resulted in early embryonic lethality.…”
Section: Shwachman-diamond Syndrome: Molecular Pathophysiologymentioning
confidence: 99%
“…5,6 Haploinsufficiency of RPS14 in the 5q-syndrome is associated with a block in the processing of pre-ribosomal RNA 4 and deregulation of ribosomal-and translation-related genes. 7 Defective ribosome biogenesis can result in a reduction in the efficiency of mRNA translation 4,8 and cultured erythroblasts from patients with the 5q-syndrome, 8 and the ribosomopathy Schwachman-Diamond syndrome, 9 exhibit impaired mRNA translation. Therefore, this defect in translation may represent a potential therapeutic target in the 5q-syndrome and other ribosomopathies.…”
mentioning
confidence: 99%
“…One potential relevant factor is the specific constitutional JAK2 haplotype, designated 46/1 or GGCC, which is correlated with JAK2V617F in cases of European descent. [6][7][8][9] We recently reported that Chinese with PMF have different clinical features than that of Europeans with PMF despite a similar frequency of JAK2V617F. 10 We sought to determine whether the JAK2 46/1 haplotype was also associated with JAK2V617F in Chinese and whether differences in the frequency of this genotype might explain different clinical phenotypes of Chinese and Europeans with PMF and other MPNs.…”
mentioning
confidence: 99%
“…Colony-forming cell assay was performed on cultured cells from one MDS patient with del(5q) and treatment with L-leucine increased the number of BFU-E colonies (Supplementary Figure 1b). Interestingly, Sen et al 14 have recently shown that treatment with L-leucine resulted in improved BFU-E colony growth in cultured cells from two of the three patients with the ribosomopathy SchwachmanDiamond syndrome.…”
mentioning
confidence: 99%